Argentine Concordat as an International Agreement Regulating the Law of Patronage - Osuchowska, Marta Zuzanna (International Studies. Interdisciplinary Political and Cultural Journal, 2020)
In the history of relations between the Argentinean government and the Holy See, two ideas are permanently intertwined: signing the Concordat and defending national patronage. The changes that occurred in the 1960s indicated that exercising the right of patronage, based on the principles outlined in the Constitution, was impossible, and the peaceful establishment of the principles of bilateral relations could only be indicated through an international agreement. The Concordat signed by Argentina in 1966 removed the national patronage, but the changes to the content of the Constitution were introduced only in 1994. The aim of the study is to show the concordat agreement concluded in 1966 by Argentina with the Holy See as an example of an international agreement. The main focus is the presentation of concordat standards for the institution of patronage. Due to the subject and purpose of the study, the work uses methods typical of social sciences in the legal science discipline. The dogmatic-legal method is the basis for consideration of the Concordat as a source of Argentine law, and as an auxiliary method, the historical-legal method was used to show the historical background of the presented issue.